Crystal Structures of Dipeptides Derived from the beta-Amino Acids (1R,2S)-2-Aminocyclopentanecarboxylic Acid and (1S,2R,3S)-2-Amino-3-methylcyclopentanecarboxylic Acid - Abraham, E; Davies, S; Roberts, P; Thompson, A; Thomson, J (2011)
Crystals of the dimeric β-peptides 13 and 20, derived from (1R,2S)-2-aminocyclopentanecarboxylic acid and (1S,2R,3S)-2-amino-3- methylcyclopentanecarboxylic acid, respectively, were synthesised and studied by X-ray diffraction in order to establish their solid state secondary structural characteristics. Compound 13 crystallises in the monoclinic space group P 2 1 with cell parameters of a = 5.2682(1) Å, b = 9.1211(2) Å, c = 22.4467(6) Å, β = 91.3855(9)°, V = 1078.29(4) Å3 and Z = 2. Compound 20 crystallizes in the orthorhombic space group P 2 1 2 1 2 1 with cell parameters of a = 5.0968(1) Å, b = 11.5546(2) Å, c = 43.5414(8) Å, V = 2564.22(8) Å3 and Z = 4. In both cases adjacent molecules are linked by a series of N-H•••O=C hydrogen bonds to form β-sheet like structures. © 2011 Springer Science+Business Media, LLC.